Linc00996 is a favorable prognostic factor in LUAD: Results from bioinformatics analysis and experimental validation - Shen, Zhenghai; Li, Xin; Hu, Zaoxiu; Yang, Yanlong; Yang, Zhenghong; Li, Shanshan; Zhou, Yongchun; Ma, Jie; Li, Hongsheng; Liu, Xi; Cai, Jingjing; Pu, Lisa; et al. (Frontiers in Genetics, 2022)
Background: Linc00996 has been reported in various cancers, but its expression level and potential role in lung adenocarcinoma (LUAD) are not fully understood. The authors investigated the expression and clinical significance of Linc00996 in LUAD and elucidated the function of its potential target genes. Materials and methods: The GEPIA database was used to explore the expression of Linc00996 across cancers. GEO and TCGA datasets were used to explore Linc00996 expression and its clinical significance in LUAD. GSEA was used to further explore the potential biological processes and pathways regulated by Linc00996 in LUAD. ssGSEA was used to explore the relationship between Linc00996 and infiltrating immune cells. Last, the clinical impact of Linc00996 was assessed in 60 patients with LUAD, and the biological functions of Linc00996 were determined by CCK8, colony formation, migration, and invasion assays. Results: We found that Linc00996 was significantly decreased in LUAD compared with adjacent normal tissues, and its downregulation was positively correlated with tumor size, lymph node metastasis, and pathological stage. Functional experiments revealed that Linc00996 inhibited LUAD cell proliferation, clonal formation, migration, and invasion in vitro. Via GSEA and ssGSEA, we found that Linc00996 might be associated with immune infiltration in LUAD, and Linc00996 might inhibit tumorigenesis and metastasis by regulating antigen processing and presentation, JAK_STAT3, and cell adhesion molecular signaling pathways. Conclusion: Linc00996 is a novel tumor suppressor in LUAD and may suppress the tumorigenesis and metastasis of LUAD via tumor-related signaling, such as antigen processing and presentation, JAK_STAT3, and cell adhesion molecular signaling pathways.